Penerapan Model Pembelajaran Kolaboratif Murder Dalam Meningkatkan Kompetensi Belajar Mata Pelajaran Pemrograman Dasar Siswa SMK Berbasis PjBL Studi Kasus : Smks Semen Gresik - Wardana Putra, Hadi; Putra Eka Prismana, I Gusti Lanang (IT-Edu : Jurnal Information Technology and Education, 2025)
This study aims to evaluate the effectiveness of implementing the collaborative learning model MURDER to enhance vocational high school students’ competencies in Basic Programming subjects using a web-based approach at SMKS Semen Gresik. The MURDER model comprises six stages: Mood (creating a positive atmosphere), Understand (grasping material), Recall (repetition), Digest (in-depth exploration), Expand (elaboration), and Review (reevaluation). It integrates Project-Based Learning methods, which place students at the center of learning by engaging them in completing real-world projects related to basic programming. The results revealed that this learning model significantly enhanced student engagement, conceptual understanding, and learning outcomes compared to conventional methods. A quantitative experimental design was applied, utilizing competency tests, observation sheets, and documentation as research instruments. Data were analyzed using descriptive statistics and t-tests. Project-Based Learning facilitates the development of critical thinking, problem-solving, and collaboration skills among students. This study not only offers an innovative alternative for educators but also provides insights into creating dynamic and conducive learning environments that prioritize critical thinking and active participation. By implementing this approach, it is expected that adaptive and technology-integrated teaching methods will become more widespread, fulfilling educational demands in the digital era. Keywords: MURDER, collaborative learning, project-based learning, Basic Programming, vocational education, learning competencies.